2012
DOI: 10.1292/jvms.11-0399
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Renal Oxalosis in a 3-Month-Old Cat Raised under Controlled Conditions

Abstract: ABSTRACT. The kidneys of a 3-month-old female cat were examined. The cat which had been raised under controlled conditions with no history of any poisoning showed progressive weight loss with increases in blood BUN and creatinine concentrations. At necropsy, both kidneys were firm in consistency with formation of focal scars. Histopathologically, widespread deposition of crystals was observed in the renal tubules (in both dilated lumina and degenerative epithelia) accompanying mild interstitial fibrosis with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In humans and cats with inherited oxalate nephrosis, the disease is seen in juveniles. 6,15,16,27,49,78 In this study, although cheetahs < 1.5 years old had significantly more crystals than older cheetahs, which might indicate an inherited predisposition, relatively large numbers of crystals were seen in cheetahs of all ages. Lesions that are characteristic of primary disease in humans and cats, including granulomatous nephritis associated with interstitial oxalates, widespread tissue oxalate deposition, 10,12,45,66,80 and neurological disease, 30,52 were not seen in the cheetahs in this study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…In humans and cats with inherited oxalate nephrosis, the disease is seen in juveniles. 6,15,16,27,49,78 In this study, although cheetahs < 1.5 years old had significantly more crystals than older cheetahs, which might indicate an inherited predisposition, relatively large numbers of crystals were seen in cheetahs of all ages. Lesions that are characteristic of primary disease in humans and cats, including granulomatous nephritis associated with interstitial oxalates, widespread tissue oxalate deposition, 10,12,45,66,80 and neurological disease, 30,52 were not seen in the cheetahs in this study.…”
Section: Discussionmentioning
confidence: 44%
“…This effect of oxalate crystals on tubular epithelium is well documented in humans and animals. 11,16,29,44,49,66,78,83 Raman spectroscopy confirmed that the majority of crystals were calcium oxalate. Melamine and other renal crystals were ruled out because the Raman spectral fingerprints did not match these compounds.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In humans, the hereditary oxalosis occurs as a result of autosomal recessive disorder in which there is abnormality of glycoxylate metabolism resulting in excess production of oxalate ions and increased absorption of oxalate ions by the gastrointestinal tract [3]. In veterinary medicine, there are a few reports on hereditary renal oxalosis in cats [26]. In humans, on the other hand, the acquired oxalosis includes 5 categories; due to excess ingestion of oxalate or oxalate producing compounds (exogenous oxalosis): increased absorption of normal dietary oxalate in enteric diseases (enteric oxalosis): oxalosis associated with chronic renal insufficiency (uremic oxalosis): excessive intake of vitamin C, and dietary insufficiency of pyridoxine and thiamine pyrophosphate (deficiency oxalosis) [3,6,22].…”
mentioning
confidence: 99%